Virological and serological characterization of critically ill patients with COVID-19 in the UK: interactions of viral load, antibody status and B.1.1.7 variant infection - Ratcliff, J; Nguyen, D; Fish, M; Rynne, J; Jennings, A; Williams, S; Al-Beidh, F; Bonsall, D; Evans, A; Golubchik, T; Gordon, AC; Lamikanra, A; et al. (Oxford University Press, 2021)
Background Convalescent plasma containing neutralizing antibody to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is under investigation for coronavirus disease 2019 (COVID-19) treatment. We report diverse virological characteristics of UK intensive care patients enrolled in the Immunoglobulin Domain of the REMAP-CAP randomized controlled trial that potentially influence treatment outcomes.